AIPE-Active Neutral Ir(III) Complexes as Bi-Responsive Luminescent Chemosensors for Sensing Picric Acid and Fe3+ in Aqueous Media - Qinglong Zhang; Jiangchao Xu; Qiang Xu; Chun Liu (Chemosensors)
Three neutral iridium complexes Ir1–Ir3 were synthesized using diphenylphosphoryl-substituted 2-phenylpyridine derivatives as the cyclometalating ligand and picolinic acid as the auxiliary ligand. They exhibited significant aggregation-induced phosphorescent emission (AIPE) properties in H2O/THF and were successfully used as bi-responsive luminescent sensors for the detection of picric acid (PA) and Fe3+ in aqueous media. Ir1–Ir3 possesses high efficiency and high selectivity for detecting PA and Fe3+, with the lowest limit of detection at 59 nM for PA and 390 nM for Fe3+. Additionally, the complexes can achieve naked-eye detection of Fe3+ in aqueous media. Ir1–Ir3 exhibit excellent potential for practical applications in complicated environments. The detection mechanism for PA is attributed to photo-induced electron transfer (PET) and Förster resonance energy transfer (FRET), and the detection mechanism for Fe3+ may be explained by PET and the strong interactions between Fe3+ and the complexes.